FUNCTIONAL TYPOLOGY AND CLASSIFICATION OF CITIES IN THE FERGANA ECONOMIC REGION - Ne’matova, Madinabonu Abdusattorovna (SCIENCE and SOCIETY, 2026)
The article analyzes the formation, functional structure, and demographic development characteristics of the cities of the Fergana Economic Region. The study assesses the position of cities within the regional urban system, their hierarchical structure, and demographic potential, and develops an authorial classification based on population size. The findings provide an important methodological basis for the scientific assessment of urban development, territorial planning, as well as the determination and evaluation of the urban livability index.